Empowering Residents of RW 01 Sukamulia through MSME-Based Entrepreneurship Training to Enhance Local Economic Resilience - Achmad Tarmizi; Dian Meliantari; Agung Suprayitno (Manunggal Halim Jaya, 2026)
This community service program aims to empower residents of RW 01 Sukamulia, Kemayoran District, Central Jakarta through entrepreneurship training based on local MSME products. Preliminary assessment indicated that many residents were engaged in small-scale home-based enterprises but faced constraints related to limited entrepreneurial knowledge, weak financial management, inadequate product packaging and branding, and low utilization of digital marketing platforms. The program was implemented using a participatory capacity-building approach that integrated entrepreneurship education, simple business management, product development, packaging and branding improvement, and digital marketing training. Evaluation was conducted through pre- and post-training assessments, direct observation of product improvements, and follow-up monitoring of early business performance. The results indicate improvements in participants’ entrepreneurial understanding, enhanced product presentation, and initial adoption of digital marketing practices. These outcomes suggest that locally grounded entrepreneurship training can contribute to strengthening MSME capacity and supporting community-based economic empowerment in urban settings.